2017
DOI: 10.1186/s12902-017-0221-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, parathyroid hormone and metabolic syndrome – the PORMETS study

Abstract: BackgroundVitamin D (VitD) and parathyroid hormone (PTH) play important roles in calcium metabolism and skeletal homeostasis. Estimates of the VitD status in several European countries show large variations between them. In addition, no national population-based estimate has been published. VitD and PTH may also play important roles in cardiovascular risk, which has been suggested to be associated with metabolic syndrome (MetS) and is very prevalent in Portugal.The goal of our study was to evaluate the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 36 publications
3
48
0
3
Order By: Relevance
“…A research study had presented that the levels of serum 25(OH)D have a positive relationship with the levels of LDL-C, TC, and HDL-C, and negative association between the levels of 25(OH)D and serum levels of TG. However, the outcomes obtained from another study were completely different and suggested a negative association between levels of TG, TC, and LDL-C, while the relationship between HDL-C and 25(OH)D was found positive and significant [13].…”
Section: Literature Reviewmentioning
confidence: 81%
“…A research study had presented that the levels of serum 25(OH)D have a positive relationship with the levels of LDL-C, TC, and HDL-C, and negative association between the levels of 25(OH)D and serum levels of TG. However, the outcomes obtained from another study were completely different and suggested a negative association between levels of TG, TC, and LDL-C, while the relationship between HDL-C and 25(OH)D was found positive and significant [13].…”
Section: Literature Reviewmentioning
confidence: 81%
“…Vitamin D deficiency has been linked to a variety of health problems from bone diseases to chronic diseases, such as MetS [ 42]. In the present longitudinal study, the association between vitamin D status and MetS development after 12 years follow up of Iranian adults was not established.…”
Section: Discussionmentioning
confidence: 55%
“…The primary outcome of analyses was the metabolic syndrome (MetS) severity score, which was calculated for participants using equations based on waist circumference, serum high-density lipoprotein, triglycerides, systolic blood pressure (not diastolic), and fasting blood glucose, as described previously [17]. Serum parathyroid hormone concentration was an independent variable; the normal serum PTH range is 15-65 pg/ml [11], thus elevated PTH was defined as > 65 pg/ml. Potentially moderating variables included daily total nutrient intake (energy, protein, total sugars, total fat, total saturated fatty acids, and cholesterol), daily mineral intake (Kalzium, magnesium, and phosphorus), daily supplements (vitamin A, vitamin D), caffeine consumption, and behavior and lifestyle factors (physical activity and alcohol consumption).…”
Section: Main Outcomesmentioning
confidence: 99%
“…In addition, 25-hydroxyvitamin D, or 25(OH)D, is an indicator of vitamin D status that is associated with Kalzium homeostasis, insulin resistance, obesity, dyslipidemia, and bone metabolism [10]. It has also been shown to have a fairly consistent inverse relationship with MetS [5,11], although the association between MetS and low serum vitamin D varies between ethnic groups [12][13][14].…”
Section: Introductionmentioning
confidence: 99%